Fuzzy logic based control of switched reluctance motor to reduce torque ripple - Derdiyok, A; Inanc, N; Ozbulur, V; Pastaci, H; Bilgic, MO (SPRINGER-VERLAG BERLIN, 1997)
This paper presents torque ripple reduction of Switched Reluctance Motor (SRM) by using fuzzy speed controller. In this purpose, current control is applied with fuzzy speed controller. Fuzzy controller adjusts value of reference current to keep speed constant. In this study, the nonlinear model of SRM is used and the motor used in simulation is a 8/6 SRM with C-Dump converter.
Keywords: Computer Science